Hypoglycemia and overtreatment of diabetes in elderly subjects: observations from 3 studies over a period of 12 years - Martial Coutaz (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
Purpose: Despite recent new recommendations from professional societies regarding the management of diabetes in older adults, it is clear that in routine practice, treatment targets are often ill-suited to the health state of polymorbid elderly diabetic patients. Methods and results: Over these last 12 years, we have performed one prospective and two retrospectives studies investigating the treatment of diabetes in our 200-bed Geriatric Care unit.